Fungicidal Effects of Chloroform Extract of Red Galangal (Alpinia purpurata (Vieill.) K. Sch) on the Growth of Trichophyton rubrum - Nur Asy Syifa Azizah; Anny Thuraidah; Ratih Dewi Dwiyanti (Tropical Health and Medical Research, 2022)
Trichophyton rubrum is the most common causative agent of anthropophilic dermatophytosis worldwide. Treatment of dermatophytosis can use natural ingredients. In Indonesia, several medicinal plants have been used, one of which is red galangal (Alpinia purpurata (Vieill.) K. Sch). This study aims to determine the effectiveness of red galangal rhizome chloroform extract on the growth of Trichophyton rubrum. This study is a True Experiment study with Posttest Only With Control Group Design consisting of 8 treatments namely positive control, extract control, 0 mg/mL (negative control), 20 mg/mL, 30 mg/mL, 40 mg/mL, 50 mg/ml, and 60 mg/mL extract of red galangal rhizome chloroform with 3 repetitions. The antifungal activity test was carried out using the determination of Minimum Inhibitory Concentration (MIC), Minimum Fungicidal Concentration (MFC), and Bioautography Test. The results showed that the red galangal rhizome chloroform extract in the Agar Overlay Bioautography Test contained an inhibition zone on the growth of Trichophyton rubrum. The determination of MIC and MFC were 20 mg/mL and 40 mg/mL, respectively. The study concludes that the red galangal rhizome chloroform extract affects the growth of the fungus Trichophyton rubrum. Research can be continued by knowing more specifics about the bioactive compounds from the red galangal rhizome, which have antifungal activity against Trichophyton rubrum.